Pengaruh Citra Merek, Kualitas Produk, Dan Harga Terhadap Kepuasan Konsumen Produk Pakaian Merek Erigo Di Kota Tangerang - Dimas Widi Laksono; Fardiana, Elvia; Rino Rinaldo (Forum Kerjasama Pendidikan Tinggi, 2023)
This research was conducted with the aim of testing and analyzing the influence of brand image, quality, product and price on consumer satisfaction of Erigo brand clothing products in the city of Tangerang. The data used in this research uses a questionnaire instrument on consumers who buy and wear Erigo brand clothing in the city of Tangerang. The number of samples collected was 100 respondents. The analysis method in this research uses qualitative primary data with the test stages carried out, namely: validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression, coefficient of determination, F test and t test. The sampling method in this research is non-probability sampling with a purposive sampling technique. The testing tool used was SPSS 25. The research results showed that the Brand Image variable partially had no significant effect on consumer satisfaction, while the Product Quality and Price variables partially had an effect on consumer satisfaction. Simultaneously, the variables Brand Image, Product Quality, and Price have a significant effect on consumer satisfaction.